1994
DOI: 10.1002/casp.2450040202
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in the local hillsborough or ‘host’ community following the Hillsborough football stadium diaster

Abstract: This paper describes levels of psychological distress and accounts of disaster among the local host community following the Hillsborough Football Stadium disaster. Thirty-two participants were interviewed 4 6 months after the event. Rates of psychological distress symptoms were high in the sample as measured by PTSD (DSM 111 criteria), Impact of Events Scale (IES) and the General Health Questionnaire (GHQ-28). The study also explores the relationships between levels of exposure, levels of distress and particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
2
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
1
4
2
2
Order By: Relevance
“…With regard to the level of general health, the number of GHQ-28 case-scorers among the present residents was similar to that found by Andersen et al [20] (χ 2 = 1.76, NS) but significantly higher than that of Wright et al [28] (χ 2 = 7.74, p < 0.01). To confirm previous studies by Raphael et al [17,18] and Hodgkinson et al [15,19], anxiety and somatization appeared to be problematic for the community residents.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…With regard to the level of general health, the number of GHQ-28 case-scorers among the present residents was similar to that found by Andersen et al [20] (χ 2 = 1.76, NS) but significantly higher than that of Wright et al [28] (χ 2 = 7.74, p < 0.01). To confirm previous studies by Raphael et al [17,18] and Hodgkinson et al [15,19], anxiety and somatization appeared to be problematic for the community residents.…”
Section: Discussionsupporting
confidence: 87%
“…However, one could say that the study on the Hillsborough Football Stadium disaster in 1989 (95 spectators were crushed to death at a football match) has given us a glimpse of how such community members could be affected. Wright, Binney and Kunkler [28] investigated the effects of the disaster upon some community members, who were neither primary nor secondary victims, living half a mile from the stadium. They found that 22% of the community sample were considered to suffer from acute PTSD according to DSM-III.…”
mentioning
confidence: 99%
“…They would also be reminded of the collision by seeing the track and the daily passing trains. Although the degree of the severity of traumatic stress in intrusion and avoidance of the residents did not appear to be greater or similar to that of Horowitz's patients who sought help for Stress Response Syndrome, the total IES score was signi®cantly higher than that of Andersen et al's 21 rescue workers (t 7.80, p 5 0.001 at 3 month follow-up; t 7.69, p 5 0.001 at 7 month follow-up), and was slightly higher than that of Wright et al's 33 Hillsborough community residents (t 0.92, ns).…”
Section: Discussioncontrasting
confidence: 63%
“…The samples also showed a high level of traumatic stress symptoms, with at least half reporting frequent intrusive thoughts. 33 In 1996, in Rickerscote, Stafford, UK, a train disaster occurred, providing an opportunity to examine the traumatic reactions of the above type of community residents. These community residents were not primary victims, in the sense that they had not been on the trains as the disaster occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Dit komt overeen met eerdere bevindingen bij omwonenden die werden blootgesteld aan een treinontsporing (Chung, Werrett, Farmer, Easthope, & Chung, 2000 ), een neergestort vliegtuig (Chung, Easthope, Eaton, & McHugh, 1999 ) en een voetbalstadionramp (Wright, Binney, & Kunkler, 1994 ). Ongeveer een kwart van de deelnemers aan onze studie had een PTSS na drieeneenhalve maand en dat komt dicht in de buurt van de 22 procent die werd gevonden bij omwonenden die zes maanden eerder de Hillsborough-voetbalstadionramp meemaakten (Wright et al, 1994 ). Symptomen van vermijding en emotionele afstomping kwamen niet veel voor, wellicht doordat de bewoners vlak bij de plaats van de ramp woonden, er veel media-aandacht was en doordat de ramp een gemeenschappelijke ervaring was.…”
Section: Beschouwingunclassified